DISPOSITION OF CEFTRIAXONE (Ro 13-9904) IN RATS (I): BLOOD LEVEL PROFILES, TISSUE DISTRIBUTION AND EXCRETION OF 14C-CEFTRIAXONE - TOMISAWA, HIROKI; ICHIHARA, SHIGEYASU; TAHARA, HITOSHI; TATEISHI, MITSURU; HEINTZ, R.; FUKAZAWA, HIDEO (CHEMOTHERAPY, 1984)
Blood level profile, tissue distribution and excretion of ceftriaxone (CTRX, Ro 13-9904), a new synthetic cephalosporin antibiotic, were examined in rats after a single intravenous injection of 14 C-ceftriaxone (14C-CTRX) at a dose of 20 mg/kg. 1. Blood level profile: A blood concentration of 14C-radioactivity was rapidly decreased over the first 4 hr after the i.v. injection (the level at the 4th hr was as low as 1/37 (male rats) 1/28 (female) of the 5-min level), while after the 4th hr, relatively slow decline curve was observed. The blood level of the intact drug represented a monophasic decline curve with a half time of 40 min between 30 min and 4 hr. 2. Tissue distribution: The highest 14C-radioactivity was observed in intestine (including its contents) and then in kidney and blood at each time point. The 14C-radioactivity in almost all the tissues examined was found to become lower with time, while the 14C in the intestine showed a peak level at the 6th hr postadministration. Elimination of 14C-radioactivity from kidney was somewhat slower when compared with the other tissues: approximately 20% of the 30-min radioactivity retained in this organ even after the 24th hr. 3. Excretion: During the initial 48 hr, nearly 40 and 50% of the dosed 14C were recovered in urine and bile, respectively, the latter was collected through a drainage inserted into the bile duct. About 90% of the radioactivity recovered in the initial 8-hr bile and in the 24-hr urine were associated with the intact drug itself.